Field evaluation of the potential for avian exposure to clothianidin following the planting of clothianidin-treated corn seed - McGee, Sean; Whitfield-Aslund, Melissa; Duca, Daiana; Kopysh, Nicole; Dan, Tereza; Knopper, Loren; Brewer, Larry (PeerJ (San Francisco, CA), 2018)
The objective of this study was to quantify consumption of clothianidin-treated corn seed by birds following standard planting practices. Based on post-planting seed counts on 21 fields in southwestern Ontario, Canada, between 29 and 813 seeds/ha (mean of 224 ± 167 (SD)) were estimated to remain on the soil surface immediately post planting (i.e., less than one seed per 10 m 2 ). This represents between 0.03 and 1.2% of the total sown seeds. The number of seeds missing on each field on the third day after planting as a result of any process (e.g., removal by foraging birds or mammals or burial as a result of heavy rains) ranged from 0 to 136 seeds/ha (0 to 0.0136 seeds/m 2 ). Behavior monitoring of individual birds and 24 h remote video surveillance were deployed to investigate how much of the treated seed remaining on the soil surface was consumed by birds. Spotting scopes were used to monitor the full duration of the field visits of 596 individual birds during morning hours for three consecutive days after planting on the 21 fields. Two birds were observed consuming treated seeds (one seed each) and three birds consumed seeds for which the treatment status could not be visually confirmed. Additionally, constant (24 h) video surveillance for 2–4 days immediately after planting was deployed at 24 areas where multiple treated seeds were found on the soil surface. Across 1,380 h of collected video footage (including both day and night periods), no birds were observed to consume any treated seeds. This study provides field evidence of two factors that determine exposure of birds to clothianidin-treated corn seeds: (1) standard sowing practices in Ontario are effective at burying treated seeds such that the proportion of sown seeds that remain on the soil surface after planting is low, and (2) birds monitored on these fields consumed very few of the clothianidin-treated corn seeds remaining on the soil surface after planting. As these results are dependent on planting techniques and seed characteristics, they are not necessarily applicable to other types of clothianidin treated seed.